1988
DOI: 10.1002/bit.260320107
|View full text |Cite
|
Sign up to set email alerts
|

A model of enzyme adsorption and hydrolysis of microcrystalline cellulose with slow deactivation of the adsorbed enzyme

Abstract: Reduction in the activity and the concentration of the adsorbed enzyme are noted in the experimental data. Two alternative mechanisms, inactivation of the adsorbed enzyme and mass transfer of the enzyme from the bulk solution to the solution within the cellulose fibril where the cellulase is assumed to be inactive, are used to represent the decline in activity. The decline in concentration of the adsorbed enzyme is represented by a modest product inhibition and, more importantly, the assumption that the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(48 citation statements)
references
References 10 publications
5
40
0
3
Order By: Relevance
“…Simultaneous saccharification and fermentation (SSF) is a well known means of reducing the product inhibition of hydrolysis. The importance of fresh adsorption of the enzyme is not well understood; however, work with purified cellulose indicates that it could be quite important (Converse et al 1988;Howell and Mangat, 1978).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous saccharification and fermentation (SSF) is a well known means of reducing the product inhibition of hydrolysis. The importance of fresh adsorption of the enzyme is not well understood; however, work with purified cellulose indicates that it could be quite important (Converse et al 1988;Howell and Mangat, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…No direct studies of this mechanism are known to the authors; it would require the development of an assay of chain ends with pure CBH. Howell and Mangat (1978) and Converse et al (1988) found it necessary to assume inactivation of the adsorbed enzyme, in addition to bulk product inhibition, to model the hydrolysis. Matsuno et al (1984) suggested that this could be due to adsorption of the enzyme components in such a way as to limit synergistic action.…”
Section: Substrate Transformationmentioning
confidence: 99%
“…In addition to equilibrium adsorption models, a dynamic adsorption model has been used by some investigators (Converse et al, 1988;Converse and Optekar, 1993;Nidetzky and Steiner, 1993;Nidetzky et al, 1994c). The Langmuir equation is widely used because it provides a good (and often very good) fit to the data in most cases, and it represents a simple mechanistic model that can be used to compare kinetic properties of various cellulase -cellulose systems.…”
Section: Cellulase Adsorption Adsorptionmentioning
confidence: 99%
“…The widely observed trend of declining rate with increasing conversion appears to be a central motivation for many models in this category. Models describing an assumed change in shape and surface area over the course of hydrolysis have been proposed (Converse and Grethlein, 1987;Converse et al, 1988;Luo et al, 1997;Movagarnjad et al, 2000;Oh et al, 2001;Philippidis et al, 1992Philippidis et al, , 1993. However, none of these models have been tested against experimental data (e.g., for surface area) to our knowledge.…”
Section: Semimechanistic Modelsmentioning
confidence: 99%
“…After a first step of adsorption onto the microfibrils, the cellulolytic enzymes are then able to cleave cellulose chains leading to substrate morphological changes. The reaction rate decreases dramatically with the extent of conversion and this slowdown could be explained by enzyme related factors such as enzyme inactivation [8,9] and product inhibition [10,11] or by changes in substrate reactivity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%